Introduction to the South African Revenue Service and National Treasury firm-level panel - Duncan Pieterse; Friedrich Kreuser; Elizabeth Gavin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The South African Revenue Service and National Treasury Firm-Level Panel is an unbalanced panel data set created by merging several sources of administrative tax data received during 2015. The four data sources that constitute the panel are: (i) company income tax from registered firms who submit tax forms; (ii) employee data from employee income tax certificates submitted by employers; (iii) value-added tax data from registered firms; and (iv) customs records from traders. These data sets constitute a significant and unique source for the study of firm-level behaviour in post-apartheid South Africa. We review the key data sources used to construct the panel, highlight some important questions that arise as a result of panel construction, discuss the biases in the resulting data, compare key aggregates in the panel to other data sources, and provide a descriptive overview of the tax records.
Keywords: C55; C80; 330; administrative data; tax; firm level